Physicochemical Characterization of Artemether-Entrapped Solid Lipid Microparticles Prepared from Templated- Compritol and Capra hircus (Goat Fat) Homolipid - Nnamani, Petra Obioma; Kenechukwu, Franklin Chimaobi; Nwagwu, Chinekwu Sheridan; Okoye, Onyinye; Attama, Anthony Amaechi (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The purpose of this study was to formulate and evaluate the physicochemical properties of artemetherloaded solid lipid microparticles (SLM) prepared from templated-compritol 888®ATO and Capra hircus (goat fat) homolipid. Various ratios of compritol 888®ATO, goat fat and Phospholipon® 90G were used to prepare the templated lipid matrices and characterized by differential scanning calorimetry (DSC). Plain and artemether-loaded SLM (0, 1.0, 3.0 and 5.0% drug) were prepared by melt-homogenization. The SLM were characterized regarding the compatibility by DSC, morphology and particle size by polarized light microscopy (PLM), encapsulation efficiency (EE%), in vitro release in simulated gastric fluid (SGF, pH 1.2), simulated intestinal fluid (SIF, pH 7.2) and alcoholic buffer (pH 3.6), and time-resolved pH-dependent stability. Stable, smooth and mostly spherical SLM with particle sizes in the range 18.77-43.79 μm and EE% ranging from 62.22% to 99.05% were obtained. DSC results showed the compatibility of drug and the formulation excipients as well as the stability of artemether in the developed SLM. Results showed significantly (p<0.05) higher drug release (88.25%) in alcoholic buffer than in SIF and SGF. By implication, incorporation of alcohol in the formulation would be a practical approach to improve artemether bioavailability from the SLM. This study has shown that the physicochemical properties of artemether were improved by SLM based on templated-compritol 888®ATO and goat fat. Dhaka Univ. J. Pharm. Sci. 20(1): 67-80, 2021 (June)